John Esten Cooke papers - Cooke, John Esten, 1830-1886.
Correspondence with Henry W. Longfellow and Samuel L. Clemens, scrapbooks, personal recollections (illustrated with original drawings), and original verses by Cooke.
Author, historian, and Confederate army officer.
Collection material in English.
Keywords: Twain, Mark, -- 1835-1910.; Longfellow, Henry Wadsworth, -- 1807-1882.; Army officers, Confederate; Authors; Historians